Investigation of advanced semiconductor materials and devices for solar cell applications - Alotaibi, Saud (2023)
High performance optoelectronic p-i-n devices based on dilute nitride GaAsPN and InGaP have been fabricated and investigated as promising III-V semiconductor materials of choice for space and photovoltaic applications due their large direct band gaps and superior radiation resistance. However, there are several factors that can introduce defects in semiconductors, including growth methods, growth conditions, substrate orientation and structure design. These defects may affect the semiconductor properties and cause severe degradations in the device performance. For solar cell applications both impurities and crystalline defects have a detrimental effect on device efficiency. Hence, identification of the defects created during the growth of materials and/or processing of these devices is necessary to gain an insight into the performance of the devices. This work investigated three sets of p-(i/n/p)-n based solar cell heterostructures and the effects on their electrical, optical and structural properties of (i) the growth conditions, namely P/Ga flux ratio (5 and 21), and rapid thermal annealing (RTA) of p-GaAs0.1P0.89N0.01 epilayers grown by molecular beam epitaxy on n-type GaP substrates, (ii) the GaAs substrate orientation (exact (100) and 20 off towards (111)B p-type GaAs substrates and doping of In0.52Ga0.48P (i-layer is either undoped and n-doped) grown by metalorganic chemical vapour deposition (MOCVD), and (iii) the GaAs misorientation angles, namely on-axis (100) semi-insulating GaAs, 2° off, 6° off, 10° off, of p-In0.52Ga0.48P grown by MOCVD. Several techniques, including atomic force microscopy, photoluminescence spectroscopy, Raman spectroscopy, Current-Voltage, Capacitance-Voltage, conventional DLTS, Laplace DLTS and Solar Simulator were used to study their surface morphology, optical, electrical and photovoltaic properties. The results showed that (i) the p-GaAs0.1P0.89N0.01 sample grown with a flux ratio of 5 exhibits superior electrical properties and lower defect density compared to the sample grown with a flux ratio of 21, (ii) n-doped In0.52Ga0.48P grown on exact (100) GaAs substrate exhibits better electrical properties with a lower ideality factor and reduced trap concentrations than the undoped and n-doped In0.52Ga0.48P samples grown on exact (100) and 20 off towards (111)B GaAs substrates, respectively, (iii) the p-In0.48Ga0.52P sample grown on exact (100) GaAs substrate demonstrates better electrical and photovoltaic properties compared to samples grown on misorientated wafers.